A COGNITIVE-PRAGMATIC MODEL OF ADDRESS UNITS IN ENGLISH AND UZBEK: A CROSS-CULTURAL COMPARATIVE ANALYSIS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This inquiry establishes a rigorous cognitive-pragmatic framework for the analysis of address units (vocatives) through a contrastive lens, focusing on the linguistic ecosystems of English and Uzbek. Despite their ubiquity in discursive space, address forms have historically been marginalized in formal linguistics, frequently reduced to mere syntactic isolates or phatic fillers. This research identifies a critical lacuna in extant scholarship: the absence of an integrative model capable of synthesizing the socio-cognitive complexities inherent in vocative selection. By leveraging principles of cognitive linguistics and sociopragmatics, this study conceptualizes address units as multi-dimensional constructs that simultaneously encode deictic centers, interpersonal hierarchies, and cultural schemas. The methodology adopts a qualitative, comparative discourse design, interrogating a heterogeneous corpus of literary texts, media discourse, and authentic interpersonal communication to capture the nuanced interaction dynamics often obscured by quantitative metrics. The central contribution of this research is the articulation of a "five-layer conceptual model" comprising the Core, Social, Pragmatic, Cognitive, and Discourse strata. Our findings indicate that while English address systems demonstrate a clear trajectory toward neutralization and morphological simplification, the Uzbek system remains profoundly "socially marked," utilizing a sophisticated array of honorifics and kinship-based metaphors. Specifically, we examine how the cognitive mapping of social proximity in Uzbek is linguistically reified through morphological markers such as the suffix "-jon," which functions as a deictic anchor for both respect and intimacy. This paper argues that the proposed model provides a superior heuristic for decoding the socio-structural asymmetries inherent in cross-cultural communication, thereby advancing the theoretical reach of contrastive pragmatics.